Hydrogen peroxide oxygenation of alkanes including methane and ethane catalyzed by iron complexes in acetonitrile - Shul'pin, Georgiy B; Nizova, Galina V; Kozlov, Yuriy N; Gonzalez-Cuervo, Laura; Süss-Fink, Georg (My University, 2004)
This paper describes an investigation of the alkane oxidation with hydrogen peroxide in acetonitrile catalyzed by iron(III) perchlorate (1), iron(III) chloride (2), iron(III) acetate (3) and a binuclear iron(III) complex with 1,4,7-triazacyclononane (4). The corresponding alkyl hydroperoxides are the main products. Nevertheless in the kinetic study of cyclohexane oxidation, the concentrations of oxygenates (cyclohexanone and cyclohexanol) were measured after reduction of the reaction solution with triphenylphosphine (which converts the cyclohexyl hydroperoxide to the cyclohexanol). Methane and ethane can be also oxidized with TONs up to 30 and 70, respectively. Chloride anions added to the oxidation solution with 1 activate the perchlorate iron derivative in acetonitrile, whereas the water as additive inactivates 2 in the H2O2 decomposition process. Pyrazine-2-carboxylic acid (PCA) added to the reaction mixture decreases the oxidation rate if 1 or 2 are used as catalysts, whereas compounds 3 and 4 are active as catalysts only in the presence of small amount of PCA. The investigation of kinetics and selectivities of the oxidations demonstrated that the mechanisms of the reactions are different. Thus, in the oxidations catalyzed by the 1, 3+PCA and 4+ PCA systems the main oxidizing species is hydroxyl radical, and the oxidation in the presence of 2 as a catalyst has been assumed to proceed (partially) with the formation of ferryl ion, (Fe-IV=O)(2+). In the oxidation catalyzed by the 4+PCA system (TONs attain 240) hydroxyl radicals were generated in the rate-determining step of monomolecular decomposition of the iron diperoxo adduct containing one PCA molecule. A kinetic model of the process which satisfactorily describes the whole set of experimental data was suggested. The constants of supposed equilibriums and the rate constant for the decomposition of the iron diperoxo adduct with PCA were estimated.
Keywords: alkanes; alkyl hydroperoxides; hydrogen peroxide; iron complexes; methane; oxidation; BRIDGED DIIRON(III) COMPLEXES; CYTOCHROME P450-CATALYZED HYDROXYLATION; DINUCLEAR IRON(III) COMPLEXES; TRANSITION-METAL-COMPLEXES; CATALASE-LIKE ACTIVITIES; HIGH-VALENT IRON; C-H BOND; SATURATED-HYDROCARBONS; ATMOSPHERIC OXYGEN; FENTON CHEMISTRY